Analisis Kestabilan Lereng Lowwall Pada Penambangan Batugamping di PT Semen Baturaja (Persero) Tbk Kabupaten Ogan Komering Ulu Provinsi Sumatera Selatan - Mataheru, Juan Aknes; Wardana , Novandri Kusuma; Isjudarto, Agustinus (ReTII, 2023)
Andesite rock is an igneous rock that has an important role in the construction of buildings, infrastructure and roads with various advantages. the quality of andesite must also meet certain requirements set out in SNI 03-0394-1989. From the results of the compressive strength test on 4 samples, the average value of compressive strength on andesite rock was 925.18 kg/cm². From the shear resistance test conducted on 2 samples, the average value of shear resistance was 17.59%. This water absorption test was carried out on 2 samples of andesite rock aggregates which resulted in an average value of 1.835%. Petrographic analysis of the 4 samples was carried out at 10x ocular magnification and 5x objective magnification contains the mineral plagioclase 35% – 45%, quartz 4% - 10%, chlorite 4% – 10%, calcite 4% – 15%, basic mass 37% -39%, and Opaque minerals 2% – 3%.